Plan estrategico y su relación en el crecimiento empresarial de la compañia LTDA. Mundo Office cantón Quevedo, periodo 2015-2016 - Valencia Ronquillo, Fernanda Lisseth (2016)
This research project was based developed in order to present a Strategic Plan and its relationship to the business growth of the Company Ltda., Office World Quevedo Canton period 2015-2019 it will help to strengthen corporate governance of the company, by analyzing the current situation, conducting market research, the same that was supported by an interview addressed to the manager of the company and a survey of the population of the canton Quevedo, results were analyzed, tabulated and helped the establishment of the strategic plan The development of the strategic plan established will help the management company World Office meets the objectives through the mission, vision and goals.Through an internal and external diagnosis of the current situation of the company World Office was established by identifying the strengths, weaknesses, opportunities and threats; besides the theoretical framework based on theories, concepts, variables related to the research was conducted; the methodology was identified by analyzing methods, types, techniques, research sources, population and the respective sample. Through the market survey it was determined the criteria of population on positioning World Office in the city of Quevedo managing to establish among others the importance of implementing a strategic plan that affects business growth of the company during the period from 2015 to 2019, in order to improve business processes across organizational policies to meet objectives and targets set in the plan. The results obtained will be concluded on the great potential of the business in order to market the city of Quevedo so this strength will be used to increase the portfolio of products and services. Whereas the company operates in a competitive market, so they must implement new strategies to improve the management and thus maintain a competitive advantage Keywords: Strategic Plan, Business Growth, diagnosis, management processes.